(untitled) (Historia, 2021)
In 'n 1795-publikasie, die laaste voor sy ontydige dood, het die Franse filosoof A-N. Condorcet opgemerk : (P)hilosophy and the sciences are necessarily neglected in all countries where there is an honourable occupation leading to wealth and position that is open to anyone who has a natural inclination for study.